Bestuur. V.l.n.r.: Diepenhorst (secr.), Wiarda, Bouma, Den Oever, Stokvis (vz., later ingevoegd), Gardenier, Siebelts, Kuiler, Jansen. Uit album 27, p.18 (1934)
Bestuur. V.l.n.r.: Diepenhorst (secr.), Wiarda, Bouma, Den Oever, Stokvis (vz., later ingevoegd), Gardenier, Siebelts, Kuiler, Jansen. Uit album 27, p.18.